Online Application of Science Practicum Video Based on Local Wisdom to Improve Student's Science Literacy - Wati Sukmawati; Prima Mutia Sari; Ika Yatri (Postgraduate, University of Mataram, 2022)
During the Covid-19 pandemic, all learning activities were carried out online, including practicum activities. To find out the success of practicum activities carried out online, this research was carried out. This study aims to develop a practicum learning video based on local wisdom to improve the scientific literacy of prospective elementary school teacher students. The development of learning videos based on local wisdom is a product produced by students while participating in online practicum activities. This research was conducted with a quasi-experimental method. The research subjects used were 20 fifth semester elementary school teacher education students who were selected by convenience sampling. The instrument developed in the form of multiplechoice questions as many as 20 questions that have been tested for validation and reliability and used for pretest and posttest. Data from students' pretest and posttest results were processed by stacking Rasch model analysis to determine changes in students' scientific literacy skills before and after participating in online practicum with videos based on local wisdom. Based on the results of the student's pretest and posttest analysis, data obtained from the logit value change from 1.2 to 3.2 and categorization was carried out based on the increase in scientific literacy skills, namely 20% low category, 65% moderate, and 15% high. Based on these results, online practicums with local wisdom-based learning videos are able to explore students' scientific literacy skills and can be applied to other practicums. In addition, students' technological literacy skills are also trained